Future Therapies of Wet Age-Related Macular Degeneration - Makoto Ishikawa; Daisuke Jin; Yu Sawada; Sanae Abe; Takeshi Yoshitomi (Journal of Ophthalmology)
Age-related macular degeneration (AMD) is the leading cause of blindness in the elderly population, and the prevalence of the disease increases exponentially with every decade after the age of 50 years. While VEGF inhibitors are promising drugs for treating patients with ocular neovascularization, there are limitations to their potential for improving vision in AMD patients. Thus, future therapies are required to have the potential to improve visual outcomes. This paper will summarize the future strategies and therapeutic targets that are aimed at enhancing the efficacy and duration of effect of antiangiogenic strategies.